Discovering the meaning of stress: a qualitative approach - Crowley, Michelle Laureen (Rhodes University, Faculty of Humanities, Department of Psychology, 1991)
The aim of the study was to understand the meaning of stress, and towards this end eleven individuals who claimed to have experienced the phenomenon during the six months prior to data collection were asked to describe their experience. These transcribed protocols were explicated in terms of a phenomenological praxis, and the emotional content of descriptions subjected to taxonomic analysis. In addition, a literature review for the purposes of tracing the development of contemporary stress models and related constructs was conducted. The latter critiqued current conceptualisations of stress, and attempted to highlight some important contributions. Explication in terms of phenomenological praxis identified seven central features associated with lived stress, namely, lived stress as : the perception of personal cost; a sense of entrapment; persistent coping efforts; learned helplessness; embodiment; and, poor social relations. In addition, the unfolding nature of the experience suggested stress as a continuous process of adjustment to worldly demands, and furthermore, highliJhted several variations of structure. The latter themes were used to develop a more inclusive model of lived stress as a dynamic and unfolding process. Dialogue with existing literature was able to confirm the self-world split proposed by the transactional approach to stress as legitimate, and furthermore, confirmed the primacy of cognition for the stress phenomenon. In addition, the link between stress and personality factors, psychopathological conditions and related fields of enquiry (such as anxiety and burnout) as well as more positive modes of being (such as creativity) were discussed. Furthermore, lived stress was shown to involve a threat to the individual's continued existence, both with respect to his/her the desired self and its unfolding and his/her physicality, while the presence of mutual hostility between self and world was also noted. The study concludes with reflection concerning the methodologies employed, and suggests that while qualitative and interpretive methods are both cumbersome and time consuming if rigorously applied, they do enrich the understanding of complex experiential phenomena. Finally, several suggestions are made for further research and refinement in the stress field, the most pertinent of which appears to be that of establishing the relationship between lived stress and the development of more debilitating psychopathological conditions.
Keywords: Stress (Psychology)